(untitled) (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
This paper analyzes the evolution of matte painting as a representational technique throughout history, its relationship with art and its influence on different industries linked to representation. We use a multi-case study methodology, which allows us to relate milestones and use an open approach to the analysis. Through it, we seek connections between their use in film, video games, and design, and its influence in them, which allows us to defend the figure of the matte painter as an artist.